Determinants of effective university-business collaboration: Empirical study of Saudi universities - Ahmed Naser Alrajhi; Necati Aydin (Journal of Industry-University Collaboration (JIUC), 2019)
Purpose The attention to the university-business collaboration (UBC) for its role in the knowledge-based economy is growing in many countries. In this context, the purpose of this paper is to conduct two surveys to explore the causes of low collaboration between the private sector and academia in the Kingdom of Saudi Arabia. Design/methodology/approach The first survey covers nearly 50 companies to learn their perspectives. Using the findings of the first survey, a second survey was conducted of university researchers to understand the determinants of private and public funding of research and development projects. The survey provided two types of data, namely, categorical and continuous, which were subjected to reliability and normality tests. A linear regression analysis also was utilized to explore the role of different factors on the funded projects by the two sectors. Findings There is a perception among researchers that the private sector is woefully underestimating research capacity of Saudi universities. One interesting finding is that publishing in journals from the International Scientific Indexing (ISI) is a strong predictor for government funding, but not for private funding. From the private sector perspective, publishing in ISI-indexed journals is not sufficient evidence of research capability. Moreover, high teaching load is a major obstacle in acquiring private funding, but not so for public funding. Practical implications The paper provides two main recommendations to improve collaboration. First, universities should incentivize publishing in high-impact journals more than in ISI-indexed journals to increase the faculty's research capabilities. Second, universities should reduce the teaching load of faculty involved in research projects, particularly those funded by the private sector. Originality/value The outcomes of this survey-based study are very valuable to the ecosystem of academia, business and government in general and for Saudi Arabia in particular, where there is a vital need to implement the right policies regarding UBC in the country.
Keywords: 330; Knowledge-based economy; KSA; R&D; University-business collaboration